FC5 Real time imaging of lymphocytes in ApoE−/− mouse aortic tertiary lymphoid organs. Issue 17 (26th August 2010) - Grassia, G; Dever, G J; Gordon, P; McInnes, I B; Spanbroek, R; Habenicht, A J R; Brewer, J M; Garside, P; Maffia, P
Abstract : Rationale for the study: Recent developments in imaging technologies such as multiphoton laser-scanning microscopy (MPLSM) have allowed real time in vivo imaging and analysis of immune cells interactions in the context of the immune system, providing important insight into the dynamics of a developing immune response. However, a number of technical limitations have precluded real time imaging of individual immune cells within intact atherosclerotic vessels. Here we provide a feasible protocol for MPLSM with real time imaging and analysis, at a cellular resolution, of adoptively transferred lymphocytes, in the adventitia of intact ApoE−/− mouse arteries and the associated aortic tertiary lymphoid organs (ATLOs) which have recently been implicated in the late stages of atherosclerosis ( JEM 2009;206 :233–48). Methodology: Cell suspensions were prepared from peripheral and mesenteric lymph nodes of C57BL/6 mice and labelled with Cell TrackerTM Red CMTPX (Molecular Probes). Lymphocytes were injected IV into aged ApoE−/− (80–87 weeks) recipients. Twenty four hours after transfer, excised intact mouse abdominal aortas were imaged by MPLSM and analysed by Volocity 5 software (Improvision). Results and conclusions: The use of this system enabled real time imaging of immune cells in atherosclerotic vessels at a cellular resolution. At 24 h after transfer several infiltrated lymphocytes were detectable in the ATLO in aged ApoE−/− mice. Cells showed a great motility with a mean velocity of 0.45 μm/s and a pick velocity of 1.16 μm/s. Consequently, this system could be a powerful tool to study the atherosclerotic immune responses.